Liquidity in resolution: Estimating possible liquidity gaps for specific banks in resolution and in a systemic crisis - Raschid Amamou; Andreas Baumann; Dimitrios Chalamandaris; Laura Parisi; Pär Torstensson (European Central Bank (ECB), 2020)
This paper contributes to the debate on liquidity in resolution by providing a quantitative assessment of liquidity gaps of banks in resolution in the euro area. It estimates possible ranges of liquidity gaps for significant banks under different assumptions and scenarios. The findings suggest that, while the average liquidity gaps in resolution are limited, the averages hide significant outliers. The paper thus shows that, under adverse circumstances, the instruments currently available to provide liquidity support to financial institutions in the euro area would be insufficient.
Keywords: G01; G21; G28; G33; C63; 330; Liquidity; resolution; bank runs; systemic crisis; contagion; Monte Carlo simulations